Carbon and biodiversity footprint accounting of a university restaurant - toward nature positive food sourcing? - Ikeoka, Takuto (2025)
Biodiversity loss is seen as one of the greatest risks to our society and has gained increasing attention internationally, despite its later development compared with other environmental issues, such as climate change. Human impact has contributed to the biodiversity loss significantly, and food and agriculture sectors have been especially highlighted due to their larger reliance on natural resources (e.g., land areas) through their value chains. Based on the background, this study assessed the biodiversity footprint, as well as its core contributor of carbon footprint, of the food sourcing of a university restaurant in Finland with BIOVALENT methodology, developed by University of Jyväskylä. The result indicated higher biodiversity footprints of meat and dairy products, as well as some products with higher footprints primarily on biodiversity (e.g., pulses). Potential food-replacement measures are additionally considered as scenario analysis, and the result indicated a notable effect of reducing animal-based products, as well as the significant need for additional measures other than expected dietary changes in the scenario. Those can include promoting agroecological practices and novel-food technologies. Considering the complex and systemic nature of the biodiversity impact of food, including sustainable consumption and just transition perspectives, collaborations among various stakeholders could be required. Finally, the utility of BIOVALENT in the current corporate biodiversity management context, based on emerging major frameworks, is considered. BIOVALENT, as well as other biodiversity-footprint modeling methods, could be useful for an initial rough assessment of corporate biodiversity impact, potentially backed up with site-specific assessments by approaches suggested in the major frameworks. Moreover, the comprehensive and easy-to-understand approach of species-extinction-risk assessment with BIOVALENT could be especially helpful for businesses’ (especially, SMEs’) evidence-based decision making with internal and external stakeholders, addressing significant challenges of corporate biodiversity management indicated in the literature.